Keefektifan Media Video Interaktif Terhadap Hasil Belajar IPA Pada Materi Organ Peredaran Darah Manusia Siswa Kelas V SDN Darupono Kendal - Cicik Sulistya; AY Soegeng Ysh; Joko Sulianto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the effectiveness of interactive video media on science learning outcomes on the material of blood circulation organs in humans in grade V SDN Darupono Kendal. The method used in this research is quantitative with the type of experiment using an experimental group and a control group with a posttest only control design. Technical analysis of data using interviews, observation, documentation, and tests. The results of the posttest data research for the experimental grade obtained an average of 82.4 and the control grade obtained an average of 77.6. In the t-test of knowledge aspects based on ttable 0.975 tcount = 6.504. Criteria t-test t-table that is6,504 2,00. This means that there is a significant difference between the average posttest value of the knowledge aspect in the experimental grade and the control grade.